Endoscopic submucosal dissection for early gastric cancer in a patient after left ventricular assist device implantation: A case report - Shinji Kuriki; Yoshiki Tsujii; Hirotsugu Saiki; Takahiro Amano; Ryotaro Uema; Minoru Kato; Takeo Yoshihara; Yoshito Hayashi; Hayato Hikita; Tetsuo Takehara (DEN Open)
Abstract The use of left ventricular assist device (LVAD) implantation has increased in recent years. Here, we report the first case of gastric endoscopic submucosal dissection (ESD) following LVAD implantation. A 69‐year‐old man who previously underwent LVAD implantation for severe heart failure underwent esophagogastroduodenoscopy, which revealed a 15‐mm flat‐elevated cancerous lesion at the greater curvature of the gastric angle. Before ESD, antithrombotic drugs were discontinued and replaced with 10,000 units of heparin. However, on the second day, the patient experienced dysarthria and right upper‐extremity movement disorder despite a prothrombin time/international normalized ratio (PT‐INR) of 2.01. On the fifth day, computed tomography revealed a low‐density area extending from the left corona radiata to the basal ganglia, leading to a diagnosis of acute cerebral infarction. Aspirin and warfarin were immediately restarted, while the heparin infusion was discontinued after confirming recovery of PT activity. Thereafter, the neurological abnormalities did not aggravate and a trend toward symptomatic improvement was observed. Two months later, ESD was performed under continuous warfarin administration (PT‐INR, 2.62) without heparin replacement, and the lesion was curatively resected without complications. The patient was discharged without adverse events. This case report provides useful information on the feasibility and perioperative management of ESD in patients with LVAD.